ANALISIS KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL IKATAN KIMIA - Mellyzar Mellyzar; Agus Muliaman (Lantanida Journal, 2020)
Chemical bonding is an important topic in chemistry. The chemistry students have to expert on the topic. Due to the importance of chemical bonding topic, qualitative descriptive research was conducted to analyze the students' errors in solving the chemical bond problems. The participants were 38 students of the third semester of Chemistry Education Department in one of the universities in Aceh, Indonesia. The result showed that the percentage of the students’ errors in solving the chemical bonds problems was high with an average of 69.08%, it means that the students’ ability in understanding chemical bond concepts is still low. This research concludes two things. First, the types of errors in solving chemical bonds problems are the students’ error in understanding the basic concepts of chemical bonds, lack of understanding of the concept how an element has a stable electron configuration, the mechanism of the difference in the forming of ion bonds and covalent bonds, the influence of geometric figures, the resultant molecular dipole moments, the number of electronegativity to molecular pollutants, the writing of a Lewis structure for molecules and polyatomic ions, the determining of the formal contents of each atom of a Lewis molecular structure, and the drawing of the Lewis structure. Second, the causes of students’ errors have forgotten the materials and also pre-requisite materials and inaccurate in reading and solving the problems. These results need to be considered in the learning process in order to improve students’ ability in solving chemical bond problems.